Even Digitalized Can Be Humane: Implementing the Humane-Smart Village Model - Sukarso, Sukarso; Niken Paramarti, Dasuki; Noviko, Sendy (Technium Social Sciences Journal, 2026)
The innovative, humane village model is a community where residents can efficiently utilize available resources, particularly those related to information technology, without marginalizing anyone. Studies on this model have identified key actors who are crucial to ensuring that no villager is marginalized. These actors or agents are members of the community who care about enabling other community groups to utilize advances in information technology, digitalization, or the internet through social media. This study seeks to identify these actors. Using a case study method in one village, data were collected from informants and respondents, and descriptive analysis was used to identify agents who can facilitate the implementation of the innovative humane village model. These agents are all family members, especially the younger generation in each family. These agents serve as facilitators, mediators, and even consultants for communities without access to the internet, particularly social media.